Interface composite material with multiple functions and preparation method and application thereof

CN122464751BActive Publication Date: 2026-10-09SHANDONG ACADEMY OF AGRICULTURAL SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610968964.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-09
Estimated Expiration
2046-07-01

AI Technical Summary

Technical Problem

传统磷肥(如过磷酸钙)施入土壤后,约80%的磷酸根会与土壤中的Fe3+、Al3+、Ca2+等金属离子形成难溶性沉淀或被固定吸附,导致当季利用率不足20%

Benefits of technology

在本发明中,壳聚糖季铵盐和阳离子改性纤维素两类阳离子多糖改性蒙脱石均能实现三重功能集成。二者分子结构不同,壳聚糖季铵盐为氨基多糖衍生物,阳离子改性纤维素为纤维素衍生物——但均通过阳离子交换作用,改性到蒙脱石,形成正电荷富集层,实现对植酸酶的高效固定化,促进植酸酶将土壤中植酸盐的矿化成磷酸根并通过静电作用吸附,得到磷酸根的缓释控制,从而促进植物的生长。这一结果表明,本发明的技术原理具有普适性,不局限于特定多糖骨架,为材料优化和成本控制提供了灵活空间。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122464751B_ABST
    Figure CN122464751B_ABST
Patent Text Reader

Abstract

The application discloses an interface composite material with multiple functions and a preparation method and application thereof, and belongs to the technical field of slow-release materials. The interface composite material with multiple functions comprises a layered base material, and a cationic polysaccharide modified layer intercalated between the base layers and coated on the surface; the cationic polysaccharide modified layer is enriched with phytase to form a phytase-cationic polysaccharide-silicate complex through electrostatic interaction; wherein the layered base material is a layered silicate material; the cationic polysaccharide comprises chitosan quaternary ammonium salt and / or cationic modified cellulose. Both chitosan quaternary ammonium salt and cationic modified cellulose can realize triple function integration of modified montmorillonite, and the material simultaneously has triple functions of enzyme molecule enrichment, promotion of organic phosphorus mineralization and phosphate slow release, and can be applied as an organic phosphorus mineralization preparation and a soil slow-release phosphorus fertilizer to promote plant growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sustained-release materials technology, specifically relating to a multifunctional interfacial composite material, its preparation method, and its application. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Phosphorus is one of the three essential nutrients for plant growth. When traditional phosphate fertilizers (such as superphosphate) are applied to the soil, approximately 80% of the phosphate ions will react with iron in the soil. 3+ Al 3+ Ca 2+ Metal ions form insoluble precipitates or are fixed and adsorbed, resulting in a utilization rate of less than 20% in the current season. At the same time, organic phosphorus compounds such as phytic acid (inositol hexaphosphate), which are abundant in soil and organic waste, are difficult for plants to directly absorb and utilize.

[0004] Phytase (EC 3.1.3.8) catalyzes the stepwise hydrolysis of phytic acid and its salts, releasing usable phosphate. However, free phytase is unstable in soil environments, susceptible to protease degradation, temperature fluctuations, and pH changes, and struggles to maintain an effective concentration at its activation site. Immobilization of phytase is an effective strategy to improve its stability, but existing immobilization carriers also have drawbacks. For example, while nanomaterial carriers (such as mesoporous silica and alumina) have high mechanical strength, they suffer from poor biocompatibility, resulting in significant activity loss after enzyme immobilization, and they lack phosphorus slow-release capabilities. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a multifunctional interface composite material, its preparation method, and its applications.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides an interface composite material with multiple functions, comprising a layered matrix material and a cationic polysaccharide modified layer intercalated between the matrix layers and coated on the surface; the cationic polysaccharide modified layer enriches phytase through electrostatic interaction to form a phytase-cationic polysaccharide-silicate complex. The layered matrix material is a layered silicate material; The cationic polysaccharide includes chitosan quaternary ammonium salt and / or cationic modified cellulose.

[0007] Secondly, the present invention provides a method for preparing the above-mentioned multifunctional interface composite material, comprising the following steps: When the cationic polysaccharide is chitosan quaternary ammonium salt or cationic modified cellulose, the calcium-based montmorillonite suspension and the cationic polysaccharide solution are mixed and reacted, and after post-treatment, modified silicate materials are obtained. The modified silicate material is obtained by combining it with phytase; Alternatively, when the cationic polysaccharide includes chitosan quaternary ammonium salt and cationic modified cellulose, the preparation method specifically includes: A calcium-based montmorillonite suspension and a chitosan quaternary ammonium salt solution were mixed and reacted. After centrifugation and washing, a chitosan quaternary ammonium salt modified montmorillonite intermediate was obtained. The chitosan quaternary ammonium salt modified montmorillonite intermediate was dispersed in water to obtain a suspension, which was then mixed and reacted with a cationic cellulose solution. After post-treatment, a modified silicate material was obtained. The modified silicate material is obtained by combining it with phytase.

[0008] Thirdly, the present invention provides the application of the above-mentioned multifunctional interface composite material or the multifunctional interface composite material prepared by the above-mentioned preparation method in the preparation of soil slow-release phosphate fertilizer and functional components of organic phosphate mineralization agents to promote plant growth.

[0009] One or more of the above technical solutions have the following advantages or beneficial effects: In this invention, both chitosan quaternary ammonium salt and cationic modified cellulose, two types of cationic polysaccharides, can achieve triple functional integration in montmorillonite. Although their molecular structures differ—chitosan quaternary ammonium salt is an aminopolysaccharide derivative, and cationic modified cellulose is a cellulose derivative—both are modified into montmorillonite through cation exchange, forming a positively charged enrichment layer. This enables efficient immobilization of phytase, promoting the mineralization of phytate in the soil into phosphate ions via phytase and its adsorption through electrostatic interactions, resulting in controlled phosphate release and thus promoting plant growth. This result demonstrates that the technical principle of this invention is universal, not limited to a specific polysaccharide framework, and provides flexibility for material optimization and cost control. Attached Figure Description

[0010] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0011] Figure 1 SEM image of Ca-Mnt; Figure 2 for Figure 1 The elemental analysis results for the area within the middle frame; where A is the elemental mapping and B is the elemental analysis data (EDS) in map A. Figure 3SEM image of QCS-Mnt; Figure 4 for Figure 3 The elemental analysis results for the area within the middle frame; where A is the elemental mapping and B is the elemental analysis data (EDS) in map A. Figure 5 SEM image of CC-Mnt; Figure 6 for Figure 5 The elemental analysis results for the area within the middle frame; where A is the elemental mapping and B is the elemental analysis data (EDS) in map A. Figure 7 SEM image of QCS-CC-Mnt; Figure 8 for Figure 7 The elemental analysis results for the area within the middle frame; where A is the elemental mapping and B is the elemental analysis data (EDS) in map A. Figure 9 XRD patterns of Ca-Mnt, CC-Mnt, and QCS-Mnt; Figure 10 The infrared spectrum of Ca-Mnt; Figure 11 The image shows the infrared spectrum of QCS-Mnt; in which, the pink region A represents CH 2870 cm⁻¹. -1 The pink region B represents the characteristic peak of the quaternary ammonium group; Figure 12 This is the infrared spectrum of CC-Mnt; where the pink region A represents CH 2870 cm⁻¹. -1 The pink region B represents the characteristic peak of the quaternary ammonium group; Figure 13 The infrared spectrum of QCS-CC-Mnt is shown; in the pink region A, CH 2870 cm⁻¹ is the focal length. -1 The pink region B represents the characteristic peak of the quaternary ammonium group; Figure 14 The results are for the zeta potentials of Ca-Mnt, CC-Mnt, QCS-Mnt, and QCS-CC-Mnt. Detailed Implementation

[0012] Terminology Explanation: QCS: Chitosan quaternary ammonium salt. CC: Cationic cellulose. Ca-Mnt: Calcium-based montmorillonite.

[0013] CC-Mnt: Cationic cellulose-modified montmorillonite. QCS-Mnt: Chitosan quaternary ammonium salt-modified montmorillonite. QCS-CC-Mnt: Chitosan quaternary ammonium salt-cationic cellulose synergistic modification of montmorillonite.

[0014] CEC: Cation exchange capacity. Ca-Mnt CEC: Cation exchange capacity of calcium-based montmorillonite.

[0015] Phytase-QCS-Mnt: refers to the phytase-QCS-Mnt complex, that is, the complex obtained by adsorbing phytase onto QCS-Mnt in Example 4.

[0016] Phytase-CC-Mnt: refers to the phytase-CC-Mnt complex, that is, the complex obtained by adsorbing phytase onto CC-Mnt in Example 5.

[0017] Phytase-QCS-CC-Mnt: refers to the phytase-QCS-CC-Mnt complex, that is, the complex obtained by adsorbing phytase onto QCS-CC-Mnt in Example 6.

[0018] Given the shortcomings of existing technologies, there is an urgent need to develop a bio-interface material that combines biocompatibility, enzyme activity retention, and phosphate slow-release function to achieve efficient utilization of organophosphorus resources and precise release of phosphate fertilizers. Therefore, this invention provides a phytase immobilization composite material based on cationic polysaccharide-modified layered silicate. This material simultaneously possesses the triple functions of enzyme molecule enrichment, promotion of organophosphorus mineralization, and phosphate slow-release, and can be used as an organophosphorus mineralizing agent and a soil slow-release phosphate fertilizer to promote plant growth.

[0019] In one typical embodiment, the present invention provides a multifunctional interface composite material, comprising a layered matrix material and a cationic polysaccharide modified layer intercalated between the matrix layers and coated on the surface; the cationic polysaccharide modified layer enriches phytase through electrostatic interaction to form a phytase-cationic polysaccharide-silicate complex. The layered matrix material is a layered silicate material; The cationic polysaccharide includes chitosan quaternary ammonium salt and / or cationic modified cellulose.

[0020] In some embodiments of this implementation, the layered silicate is calcium-based montmorillonite (Ca-Mnt) with a cation exchange capacity (CEC) of 50-120 mmol / 100g.

[0021] It is understood that the main component of bentonite is montmorillonite. During experiments, impurities in bentonite are generally removed by washing with water, so bentonite is essentially "montmorillonite". Therefore, the layered silicate material used in this invention is directly referred to as "montmorillonite". In addition, since sodium in sodium-based montmorillonite is harmful to soil, the natural montmorillonite used in this invention is calcium-based montmorillonite.

[0022] Specifically, the present invention provides a phytase-enriched organophosphate mineralization slow-release material, comprising a layered silicate material and a cationic polysaccharide modified layer intercalated between matrix layers and coated on the surface; the modified layer enriches phytase through electrostatic interaction to form a phytase-cationic polysaccharide-montmorillonite complex; the complex achieves controlled slow release of phosphate in soil water environment through the synergistic effect of electrostatic repulsion and ion exchange.

[0023] In some embodiments of this implementation, the degree of quaternization (i.e., the degree of substitution) of the chitosan quaternary ammonium salt is ≥90%, preferably ≥98%, and the molecular weight of each charged unit is approximately 300~350 g / mol.

[0024] In some embodiments of this implementation, the degree of quaternization of the cationic cellulose is ≥20%, preferably ≥22%. The amount of modified material used depends on the degree of quaternization. The molecular weight of the structural unit is 150~200 g / mol, preferably 190~200 g / mol, and specifically, it can be 195 g / mol.

[0025] In some embodiments of this implementation, the phytase loading is 100-500 mg / g of the composite material. The phytase activity is ≥5000 U / g.

[0026] In some embodiments of this implementation, the multifunctional interface composite material exhibits the following phosphate release rates in an aqueous environment with pH 4.0-8.0: ≤35% in 24h, preferably ≤20%; 50%~80% in 7 days, preferably ≤60%; and 70%~90% in 28 days, preferably ≤80%.

[0027] The multifunctional interface composite material exhibits a mineralization rate of 60% to 80%, preferably 68% to 80%, and more preferably 75% to 80%, in a sodium acetate-acetic acid (pH 5 to 7) solution after 24 hours; a cumulative mineralization rate of ≥80%, preferably ≥87%, and more preferably ≥95% after 7 days; and an enzyme activity retention (after 7 days) of ≥75%, preferably ≥85%.

[0028] In one typical embodiment, the present invention provides a method for preparing the above-mentioned multifunctional interface composite material, comprising the following steps: When the cationic polysaccharide is chitosan quaternary ammonium salt or cationic modified cellulose, the calcium-based montmorillonite suspension and the cationic polysaccharide solution are mixed and reacted, and after post-treatment, modified silicate materials are obtained. The modified silicate material is obtained by combining it with phytase.

[0029] In some embodiments of this implementation, the preparation method of the calcium-based montmorillonite suspension includes: dispersing calcium-based montmorillonite in water to form a suspension, and stirring at 70-90°C (specifically 70°C, 75°C, 80°C, 85°C, 90°C, etc., preferably 80°C) for 0.5-5 hours (specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc., preferably 1 hour) to allow the flakes to open. Further, the mass concentration of the calcium-based montmorillonite suspension is 1-10%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., preferably 4-6%.

[0030] In some embodiments of this implementation, the preparation method of the cationic polysaccharide solution includes: dispersing the cationic polysaccharide in water and stirring at 70~90℃ (specifically 70℃, 75℃, 80℃, 85℃, 90℃, etc., preferably 80℃) for 0.5~5h (specifically 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc., preferably 1h) until completely dissolved to form a homogeneous solution.

[0031] Specifically, when the cationic polysaccharide is chitosan quaternary ammonium salt or cationic modified cellulose, the preparation method of the chitosan quaternary ammonium salt / cationic modified cellulose solution includes: dispersing the chitosan quaternary ammonium salt / cationic modified cellulose in water and stirring at 70~90℃ (specifically 70℃, 75℃, 80℃, 85℃, 90℃, etc., preferably 80℃) for 0.5~5h (specifically 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc., preferably 1h) until completely dissolved to form a homogeneous solution. Below 60℃, the cationic polysaccharide cannot obtain a uniform suspension; above 90℃, the cationic polysaccharide structure will be destroyed at high temperatures, causing modification failure.

[0032] Furthermore, the mass concentration of the chitosan quaternary ammonium salt / cationically modified cellulose solution is 1%~10%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0033] In some embodiments of this implementation, the post-processing includes centrifugation, washing, drying, and sieving.

[0034] The post-treatment conditions are not specifically limited, as long as the desired effect is achieved. Specifically: centrifugation conditions can be 5000~10000 rpm for 5~30 min, preferably 8000 rpm for 10 min. Washing is performed multiple times with 3~5 times the volume of ice water, measuring the zeta potential of the material each time, until the zeta potential is greater than +25 mV and does not change. Drying conditions are: drying at 90~120℃ for 1~20 h, vacuum drying can be used. After grinding, pass through a 100-mesh sieve.

[0035] The reason for using ice water washing is to allow the layered structure that expands at high temperatures to close quickly, promoting the entry of more modifiers into montmorillonite.

[0036] In some embodiments of this implementation, when the cationic polysaccharide is chitosan quaternary ammonium salt and cationic modified cellulose, the preparation method specifically includes: A calcium-based montmorillonite suspension and a chitosan quaternary ammonium salt solution were mixed and reacted. After centrifugation and washing, a chitosan quaternary ammonium salt modified montmorillonite intermediate was obtained. The chitosan quaternary ammonium salt modified montmorillonite intermediate was dispersed in water to obtain a suspension, which was then mixed and reacted with a cationic cellulose solution. After post-treatment, the modified silicate material was obtained.

[0037] Furthermore, whether it's the mixing reaction of calcium-based montmorillonite suspension and chitosan quaternary ammonium salt solution or the mixing reaction after adding cationic cellulose solution, the mixing reaction conditions are: 60~100℃ (specifically 60℃, 70℃, 75℃, 80℃, 85℃, 90℃, 100℃, etc.) with stirring for 3~6h (specifically 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, etc.), preferably 70~90℃ with stirring for 3~5h, and most preferably 80℃ with stirring for 4h. At low temperatures, the interlayer structure of montmorillonite cannot be opened, and the modifier cannot penetrate; at high temperatures, the polysaccharide-modified material will thermally decompose and become ineffective.

[0038] Furthermore, when the chitosan quaternary ammonium salt modified montmorillonite intermediate is dispersed in water to obtain a suspension, a suspension with a mass fraction of 1% to 10% is prepared and stirred in a water bath at 60 to 100°C for 0.5 to 2 hours to further open up the sheets.

[0039] In some embodiments of this implementation, the amount of cationic polysaccharide used is 0.8 to 2.0 times the cation exchange capacity (Ca-Mnt CEC) of calcium montmorillonite, specifically 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc., preferably 1 to 2 times. If the amount is less than 1.0 times, the modified material has insufficient positive electrostatic attraction to phytase, resulting in poor phytase adsorption; if the amount is more than 2.0 times, the modifier is wasted.

[0040] Specifically: when the cationic polysaccharide is chitosan quaternary ammonium salt or cationic modified cellulose, its dosage is 0.8 to 2.0 times the cation exchange capacity of calcium montmorillonite; when the cationic polysaccharide is chitosan quaternary ammonium salt and cationic modified cellulose, the total dosage of chitosan quaternary ammonium salt and cationic modified cellulose is 0.8 to 2.0 times the cation exchange capacity of calcium montmorillonite, wherein the equivalent ratio of chitosan quaternary ammonium salt and cationic modified cellulose is (6 to 8):(2 to 4), specifically 6:4, 6.5:3.5, 7:3, 7.5:2.5, 8:2, etc., preferably (6.5 to 7.5):(2.5 to 3.5), and most preferably 7:3.

[0041] Chitosan quaternary ammonium salt has a high ammonium group content but is highly water-soluble, and much of it remains in the solution. Modified cellulose has a low ammonium group content but is less water-soluble, allowing more to remain on montmorillonite. The combination of the two, with cellulose forming hydrogen bonds with chitosan, effectively reduces the amount of chitosan entering the aqueous solution. The more chitosan remains in bentonite, the higher the zeta potential of the modified material, and the more phytase it can adsorb.

[0042] In some embodiments of this implementation, the specific steps of combining the modified silicate material and phytase include: The modified silicate material was dispersed in a buffer solution with a pH of 5.0 to 7.0, and then phytase solution was added for adsorption by shaking. After adsorption, the material was centrifuged, washed, and dried to obtain the phytase-cationic polysaccharide-silicate complex.

[0043] Furthermore, the mass ratio of phytase to modified silicate material is controlled to be 0.1:1 to 1:1 (specifically, it can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc., preferably 0.4:1 to 0.6:1), and adsorption is carried out by shaking at 4 to 15°C for 2 to 6 hours. The shaking conditions are 100 to 500 rpm. Drying can be performed by freeze drying.

[0044] Furthermore, the buffer solution is a 10-30 mM sodium acetate-acetic acid buffer solution (pH 5.0). The mass-to-volume ratio of the modified silicate material to the buffer solution is (0.5-2 g):(50-150 mL). When dispersing the modified silicate material in the buffer solution, ultrasonic dispersion can be used for 5-30 min.

[0045] Preferably, when the cationic polysaccharide is chitosan quaternary ammonium salt / cationically modified cellulose, the present invention provides a method for preparing the above-mentioned multifunctional interfacial composite material, comprising the following steps: (1) Disperse calcium-based montmorillonite in water to prepare a suspension with a mass fraction of 1-10% (preferably 3%-6%), and stir at 60-100°C for 0.5-5 hours to open the sheets; (2) The cationic polysaccharide (chitosan quaternary ammonium salt or cationic modified cellulose) is pre-dissolved in water at 60~100℃ to prepare a homogeneous solution with a mass fraction of 2%~10%; the amount of the cationic polysaccharide is 0.8~2.0 times the cation exchange capacity of calcium-based montmorillonite; (3) Add the solution obtained in step (2) to the suspension obtained in step (1), and stir at 60~100℃ for 3~6 hours to allow the chitosan quaternary ammonium salt to be fully intercalated and to react with the calcium-based montmorillonite layer. 2+ Ion exchange occurs; (4) The reaction product is quickly centrifuged and separated. The precipitate is washed repeatedly with 3 to 5 times ice water. The zeta potential of the material is measured each time until the zeta potential is greater than +25mV and does not change. (5) After drying, grind and sieve to obtain cationic polysaccharide-modified montmorillonite; (6) Disperse the cationic polysaccharide-modified montmorillonite in a buffer solution with pH 5.0~7.0, add phytase solution, control the mass ratio of phytase to modified montmorillonite to be 0.1:1~1:1, and shake and adsorb at 4~15℃ for 2~6h; (7) Centrifuge, wash unbound enzyme with the same buffer solution, and freeze dry to obtain phytase-cationic polysaccharide-montmorillonite complex.

[0046] Preferably, when the cationic polysaccharide is chitosan quaternary ammonium salt and cationic modified cellulose, the present invention provides a method for preparing the above-mentioned multifunctional interfacial composite material, comprising the following steps: (1) Disperse calcium-based montmorillonite in water to prepare a suspension with a mass fraction of 1-10% (preferably 3%-6%), and stir at 60-100°C for 0.5-5 hours to open the sheets; (2) Chitosan quaternary ammonium salt is pre-dissolved in water at 60~100℃ to prepare a homogeneous solution with a mass fraction of 2%~10%; the amount of the cationic polysaccharide is 0.8~2.0 times the cation exchange capacity of calcium montmorillonite; (3) Add the solution obtained in step (2) to the suspension obtained in step (1), and stir at 60~100℃ for 3~6 hours to allow the chitosan quaternary ammonium salt to be fully intercalated and to react with the calcium-based montmorillonite layer. 2+ Ion exchange occurs; (4) The reaction product is quickly centrifuged and separated. The precipitate is washed repeatedly with 3 to 5 times ice water. The zeta potential of the material is measured each time until the zeta potential is greater than +25mV and does not change. (5) The material obtained in step (4) is further modified with cationic cellulose. If the zeta potential of the material is greater than +40mV, the material is qualified. (6) After drying, the material is ground and sieved to obtain chitosan quaternary ammonium salt-cationic cellulose synergistic modification of montmorillonite. Chitosan quaternary ammonium salt has a relatively small molecular weight and low branching degree, making it easier to intercalate into the interlayer of montmorillonite and expand the interlayer spacing of montmorillonite. The cationic cellulose has a long molecular chain and good rigidity, and is mainly adsorbed on the outer surface of the particles and the interlayer edge, providing spatial stability. When the two are synergistically modified, a denser organic coating layer can be formed, which can improve the positive charge density (zeta potential) of the modified material.

[0047] (7) Chitosan quaternary ammonium salt-cationic cellulose synergistic modified montmorillonite was dispersed in a buffer solution with pH 5.0~7.0, phytase solution was added, and the mass ratio of phytase to modified montmorillonite was controlled to be 0.1:1~1:1. The mixture was shaken and adsorbed at 4~15℃ for 2~6h. (8) Centrifuge, wash unbound enzyme with the same buffer solution, and freeze dry to obtain phytase-cationic polysaccharide-montmorillonite complex.

[0048] In one typical embodiment, the present invention provides the application of the above-mentioned multifunctional interface composite material or the multifunctional interface composite material prepared by the above-mentioned preparation method in the preparation of soil slow-release phosphate fertilizer and functional components of organophosphate mineralization agents to promote plant growth.

[0049] Preferably, the material can be prepared into a compound fertilizer with urea, potassium sulfate, phytate, etc.

[0050] In this invention, unless otherwise specified, all other test materials and instruments are conventional test materials in the field and can be purchased through commercial channels.

[0051] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0052] Example 1: Preparation of chitosan quaternary ammonium salt modified montmorillonite (QCS-Mnt) 10 g of calcium-based montmorillonite (Ca-Mnt, cation exchange capacity 57.82 mmol / 100g) was dispersed in 200 mL of deionized water to prepare a suspension with a mass fraction of 4.8%, and placed in an 80℃ water bath for pre-swelling for 1 hour, during which magnetic stirring was continuously applied.

[0053] 2.4 g of chitosan quaternary ammonium salt (QCS, degree of quaternization ≥98%, molecular weight of each charged unit approximately 312 g / mol, equivalent to 1.3 times the equivalent of Ca-Mnt CEC) was dissolved in 100 mL of deionized water and magnetically stirred at 80 °C until completely dissolved to form a homogeneous solution.

[0054] The QCS solution was slowly added dropwise to the Ca-Mnt suspension, and the mixture was stirred continuously at 80°C for 4 hours. After the reaction was complete, the mixture was transferred to a centrifuge tube and centrifuged at 8000 rpm for 10 minutes, discarding the supernatant. The precipitate was washed rapidly with 3-5 times its volume of ice water by centrifugation 2-3 times, measuring the zeta potential of the material each time, until the zeta potential was greater than +25 mV and remained unchanged. The washed product was dried in a vacuum drying oven to constant weight, ground, and passed through a 100-mesh sieve to obtain chitosan quaternary ammonium salt modified montmorillonite, denoted as QCS-Mnt.

[0055] Example 2: Preparation of cationic cellulose-modified montmorillonite (CC-Mnt) 10 g of calcium-based montmorillonite (Ca-Mnt, cation exchange capacity 57.82 mmol / 100 g) was dispersed in 200 mL of deionized water to prepare a suspension with a mass fraction of 4.8%, and then pre-swelled in an 80°C water bath for 1 hour.

[0056] 6.8 g of cationic cellulose (CC, structural unit molecular weight 195 g / mol, degree of quaternization ≥22%, equivalent to 1.3 times the equivalent of Ca-Mnt CEC) was dissolved in 100 mL of deionized water and magnetically stirred at 80 °C until completely dissolved to form a homogeneous solution.

[0057] The CC solution was slowly added dropwise to the Ca-Mnt suspension, and the mixture was stirred continuously at 80°C for 4 hours. Subsequent centrifugation, washing, drying, and sieving were performed as in Example 1 to obtain cationic cellulose-modified montmorillonite, denoted as CC-Mnt.

[0058] Example 3: Preparation of chitosan quaternary ammonium salt-cationic cellulose synergistic modification of montmorillonite (QCS-CC-Mnt) 10 g of calcium-based montmorillonite (Ca-Mnt, cation exchange capacity 57.82 mmol / 100g) was dispersed in 200 mL of deionized water to prepare a suspension with a mass fraction of 4.8%, and placed in an 80℃ water bath for pre-swelling for 1 hour, during which magnetic stirring was continuously applied.

[0059] 1.82 g of chitosan quaternary ammonium salt (QCS, degree of quaternization ≥98%, molecular weight of each charged unit approximately 312 g / mol, equivalent to 0.91 times the equivalent of Ca-Mnt CEC, accounting for 70% of the total modifier equivalent) was dissolved in 100 mL of deionized water and magnetically stirred at 80 °C until completely dissolved to form a homogeneous solution.

[0060] The QCS solution was slowly added dropwise to the Ca-Mnt suspension, and the mixture was stirred continuously at 80°C for 4 hours to allow the QCS to fully intercalate and interact with the interlayer Ca. 2+ Ion exchange occurs. After the reaction is complete, the mixture is transferred to a centrifuge tube and centrifuged at 8000 rpm for 10 minutes, discarding the supernatant. The precipitate is washed rapidly with 3-5 times its volume of ice water by centrifugation 2-3 times, measuring the zeta potential of the material each time, until the zeta potential is greater than +25 mV and does not change, yielding the chitosan quaternary ammonium salt modified montmorillonite intermediate.

[0061] The above intermediate was redispersed in 200 mL of deionized water to prepare a suspension with a mass fraction of approximately 4.8%, and then stirred in an 80°C water bath for 1 hour to further open the film.

[0062] 2.04 g of cationic cellulose (CC, degree of quaternization ≥22%, equivalent to 0.39 times the equivalent of Ca-Mnt CEC, accounting for 30% of the total modifier equivalent) was dissolved in 100 mL of deionized water and magnetically stirred at 80 °C until completely dissolved to form a homogeneous solution.

[0063] The CC solution was slowly added dropwise to the QCS-Mnt suspension, and the mixture was stirred continuously at 80°C for 4 hours to allow the CC to further intercalate and interact with the remaining interlayer Ca. 2+ Ion exchange occurs, and a synergistic interlayer structure is formed with the intercalated QCS. After the reaction, the mixture is transferred to a centrifuge tube and centrifuged at 8000 rpm for 10 minutes, discarding the supernatant. The precipitate is washed rapidly with 3-5 times its volume of ice water by centrifugation 2-3 times, measuring the zeta potential of the material each time, until the zeta potential is greater than +40 mV and remains unchanged. The washed product is dried in a vacuum drying oven at 105℃ to constant weight, ground, and passed through a 100-mesh sieve to obtain chitosan quaternary ammonium salt-cationic cellulose synergistic modified montmorillonite, denoted as QCS-CC-Mnt.

[0064] Figure 1 , Figure 3 , Figure 5 and Figure 7SEM images of Ca-Mnt, QCS-Mnt, CC-Mnt, and QCS-CC-Mnt are shown. The SEM images before and after modification reveal that calcium-based montmorillonite itself does not contain carbon; only the modified material contains carbon. The higher the carbon content of the material, the better the adsorption of phytase. The synergistically modified material has the highest carbon content.

[0065] XRD results showed that the interlayer spacing of QCS-Mnt increased from 1.48 nm in Ca-Mnt to 1.52 nm; and the interlayer spacing of CC-Mnt increased to 1.485 nm, both confirming successful intercalation of cationic polysaccharides.

[0066] FTIR shows: QCS-Mnt at 1480 cm⁻¹ -1 A characteristic peak of quaternary ammonium groups appeared at 1485 cm⁻¹; CC-Mnt showed a peak at 1485 cm⁻¹. -1 A corresponding peak appears at 1050 cm⁻¹. -1 The stretching vibration of cellulose COC is enhanced at 1450 cm⁻¹. QCS-CC-Mnt at 1450 cm⁻¹ -1 An ammonium group peak also appeared at 1050 cm⁻¹, but it was not as pronounced as in QCS-Mnt. -1 The presence of weak cellulose COC stretching vibrations indicates that both materials have entered montmorillonite.

[0067] Zeta potential: QCS-CC-Mnt, QCS-Mnt, and CC-Mnt exhibited potentials of +55.7 mV, +45.05 mV, and +27.43 mV, respectively, at pH 6.0, all significantly higher than Ca-Mnt's -25.88 mV. Higher zeta potentials indicate greater adsorption capacity for negatively charged phytases.

[0068] Example 4: Preparation of phytase-QCS-Mnt complex 1.0 g of QCS-Mnt obtained in Example 1 was dispersed in 100 mL of 50 mM sodium acetate-acetic acid buffer (sodium acetate-acetic acid, pH 6.0) and sonicated for 10 minutes. 0.5 g of phytase (derived from Aspergillus niger, enzyme activity ≥5000 U / g) was added to achieve a phytase to QCS-Mnt mass ratio of 0.5:1. The mixture was placed in a 4°C constant-temperature shaker and shaken at 150 rpm for 3 hours for adsorption.

[0069] After adsorption, the solid phase was separated by centrifugation at 8000 rpm for 10 minutes, and the precipitate was washed twice with the same sodium acetate-acetic acid buffer. The phytase-QCS-Mnt complex was obtained by freeze-drying and designated Phytase-QCS-Mnt.

[0070] The phytase loading was determined to be 320 mg / g using a BCA kit.

[0071] Example 5: Preparation of phytase-CC-Mnt complex 1.0 g of CC-Mnt obtained in Example 2 was dispersed in 100 mL of sodium acetate-acetic acid (pH 6.0), and 0.5 g of phytase (enzyme / CC-Mnt mass ratio of 0.5:1) was added. The mixture was shaken at 4°C for 3 hours for adsorption. Subsequent separation and washing steps were the same as in Example 4.

[0072] The phytase loading was determined to be 280 mg / g using a BCA kit.

[0073] Example 6: Preparation of phytase-QCS-CC-Mnt complex 1.0 g of QCS-CC-Mnt obtained in Example 3 was dispersed in 100 mL of 50 mM sodium acetate-acetic acid buffer (pH 6.0) and sonicated for 10 minutes. 0.5 g of phytase (derived from Aspergillus niger, enzyme activity ≥ 5000 U / g) was added to achieve a phytase to QCS-CC-Mnt mass ratio of 0.5:1. The mixture was placed in a 4°C constant-temperature shaker and shaken at 150 rpm for 3 hours for adsorption.

[0074] After adsorption, the solid phase was separated by centrifugation at 8000 rpm for 10 minutes, and the precipitate was washed twice with the same sodium acetate-acetic acid buffer. The phytase-QCS-CC-Mnt complex was obtained by freeze-drying and denoted as Phytase-QCS-CC-Mnt.

[0075] The phytase loading was determined to be 410 mg / g using a BCA kit.

[0076] Example 7: Comparative Test of Organophosphorus Mineralization Performance Weigh out 1.03 g of Phytase-QCS-CC-Mnt, 1.24 g of Phytase-QCS-Mnt, 1.37 g of Phytase-CC-Mnt, 700 mg of soil, and 300 mg of free phytase, respectively, and add them to 100 mL of 5 mM sodium phytate solution (sodium acetate-acetic acid, pH 6.0). The reaction was carried out at 37 °C with constant temperature and shaking. The phosphate concentration was determined by the molybdenum blue colorimetric method and the sodium phytate mineralization rate was calculated.

[0077] Table 1. Organophosphorus mineralization properties of different materials

[0078] Both the QCS-Mnt and CC-Mnt immobilization systems were significantly superior to soil-free enzymes, maintaining stable mineralization within 7 days. Among them, the QCS-CC-Mnt synergistic immobilization system had the highest enzyme loading (410 mg / g) and the optimal interfacial microenvironment, resulting in the highest mineralization efficiency. The cumulative mineralization rate reached 96% within 7 days, and the enzyme activity retention rate reached 85%, which was significantly better than the single modification system.

[0079] Example 8: Comparative Test of Phosphate Releasing Performance 0.5 g of Phytase-QCS-CC-Mnt, Phytase-QCS-Mnt, and Phytase-CC-Mnt were placed in dialysis bags, and 200 mg P / g of sodium phytate was added. The bags were then immersed in 500 mL of aqueous solution and shaken at 37 °C. The amount of phosphate leaching was measured using the molybdenum blue colorimetric method (ELISA reader), and the release rate was calculated.

[0080] Table 2. Phosphate release performance of different materials

[0081] The QCS-CC-Mnt synergistic modification system has the highest positive charge and the strongest electrostatic adsorption and physical barrier effect on phosphate, and its sustained-release performance is significantly better than that of the single modification system: the initial release rate at 24 h is only 18%, and the cumulative release rate at 28 days drops to 77%, showing the best sustained-release effect.

[0082] Example 9: Soil incubation and verification of biological effects Phytase-QCS-CC-Mnt, Phytase-QCS-Mnt, and Phytase-CC-Mnt were applied to the potting soil at a dosage equivalent to 0.1 g / kg soil of P2O5, along with sodium phytate (an equal amount of P2O5). A blank control (no phosphate fertilizer) and a control with only QCS-Mnt (no enzyme) were also included. Ten wheat seeds were sown in each pot and cultured in a greenhouse until single-season maturity (approximately 120 days), under standard management.

[0083] Table 3 Results of Harvest Period Measurement

[0084] The available phosphorus content in the soil treated with Phytase-QCS-Mnt, Phytase-CC-Mnt, and Phytase-QCS-CC-Mnt increased by 9.72%, 5.30%, and 24.51%, respectively, compared to the sodium phytate-only group. Wheat grain yield in the three treatment groups increased by 66.63%, 22.71%, and 77.45%, respectively, compared to the sodium phytate-only group. The Phytase-QCS-CC-Mnt synergistic immobilization system showed the best performance in the soil-plant system.

[0085] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A multifunctional interface composite material, characterized in that, It includes a layered matrix material and a cationic polysaccharide modified layer intercalated between the matrix layers and coated on the surface; the cationic polysaccharide modified layer enriches phytase through electrostatic interaction to form a phytase-cationic polysaccharide-silicate complex; The layered matrix material is calcium-based montmorillonite; the cation exchange capacity is 50~120 mmol / 100g. The cationic polysaccharide is a chitosan quaternary ammonium salt and cationic modified cellulose; The equivalent ratio of chitosan quaternary ammonium salt to cationic modified cellulose is (6~8):(2~4); the total amount of chitosan quaternary ammonium salt and cationic modified cellulose is 0.8~2.0 times the cation exchange capacity of calcium-based montmorillonite; The degree of quaternization of the chitosan quaternary ammonium salt is ≥90%, and the molecular weight of each charged unit is 300-350 g / mol; The degree of quaternization of the cationic cellulose is ≥20%; The phytase loading is 100~500 mg / g of the cationic polysaccharide-silicate complex material.

2. A method for preparing a multifunctional interface composite material as described in claim 1, characterized in that, Includes the following steps: A modified silicate material was obtained by mixing and reacting a calcium-based montmorillonite suspension with a cationic polysaccharide solution and then post-processing it. The modified silicate material is obtained by combining it with phytase; The preparation method of the calcium-based montmorillonite suspension includes: dispersing calcium-based montmorillonite in water and stirring at 70~90℃ for 0.5~5h; The method for preparing the cationic polysaccharide solution includes: dispersing the cationic polysaccharide in water and stirring at 70-90°C for 0.5-5 hours until completely dissolved to form a homogeneous solution; The modified silicate material is prepared by mixing and reacting calcium-based montmorillonite suspension and chitosan quaternary ammonium salt solution, and then obtaining chitosan quaternary ammonium salt modified montmorillonite intermediate after centrifugation and washing. The chitosan quaternary ammonium salt modified montmorillonite intermediate was dispersed in water to obtain a suspension, which was then mixed and reacted with a cationic cellulose solution. After post-treatment, a modified silicate material was obtained. The post-processing includes centrifugation, washing, drying, and sieving; The conditions for the mixed reaction are: stirring at 60~100℃ for 3~6 hours; The specific steps of the modified silicate material and phytase composite include: dispersing the modified silicate material in a buffer solution with pH 5.0~7.0, adding phytase solution and shaking for adsorption, and centrifuging, washing and drying after adsorption to obtain the phytase-cationic polysaccharide-silicate composite. The mass ratio of phytase to modified silicate material is 0.1:1 to 1:1; The buffer solution includes sodium acetate-acetic acid buffer.

3. The preparation method according to claim 2, characterized in that, When the chitosan quaternary ammonium salt modified montmorillonite intermediate is dispersed in water to obtain a suspension, it is placed in a water bath at 60~100℃ and stirred for 0.5~5h.

4. The application of the multifunctional interface composite material of claim 1 or the multifunctional interface composite material prepared by the preparation method of claim 2 or 3 in the preparation of soil slow-release phosphate fertilizer and functional components of organic phosphate mineralization agents to promote plant growth.

Citation Information

Patent Citations

  • Preparation method and application of montmorillonoid based inorganic-organic hybrid fire retardant

    CN106893143A